The impact of standardized huddle tools on case duration in pediatric microlaryngoscopy/bronchoscopy. (January 2022) - Lavin, Jennifer; Walker, Austin; Thompson, Dana M.; Valika, Taher; Jones, Roderick C.; Mathew, Reba; Brave, Kent; Ida, Jonathan
Abstract: Objective: Equipment necessary to perform pediatric microlaryngoscopy/bronchoscopy (MLB) varies considerably depending on the selected interventions. In procedures with equipment variability, surgical case length may be increased due to the need to procure items intraoperatively. We hypothesized that use of standardized huddle tools listing necessary equipment would be associated with a shortened case duration in MLB. Methods: As part of a quality improvement initiative at our academic, tertiary care pediatric hospital, a standardized huddle sheet was created that listed options of equipment for MLB. Listed items included telescope/bronchoscope size, laryngoscope selection, interventional equipment, suspension, microscopes, and topical medications. The tool was completed by otolaryngology and shared with the circulating nurse at the beginning of the day so equipment needs could be anticipated. The tool was introduced to staff in November 2017 and to trainees in February 2018. To assess intervention impact, monthly median surgical case duration and room turnover time were retrospectively tracked using control chart analysis from March 2017 to June 2019. Results: At baseline, the centerline case duration was 49 min. Two months following introduction of the huddle sheet to trainees, the centerline duration decreased to 43 min. This change was sustained throughout the period studied. No changes in room turnover time were observed during this period. Conclusions: Standardized huddle tool use prior to MLB was associated with a median decrease of 6 min of operating room time without a change in operating room turnover time. Use of similar tools in procedures with significant equipment variability may be beneficial.